Nanoelectronic biosensing of dynamic cellular activities - Pui, Tze Sian (2011)
Detecting dynamic cellular activities such as exocytosis and bioelectricity is important in the field of molecular biology and medicine. Comparing to conventional biochemical assay, biophysical measurements, and optical methods, electronic biosensing based on nanomaterials have shown promising platform in resolving rapid biological events with ultra sensitivity, high spatial and temporal resolution. Here, we use silicon nanowire (SiNW) and single walled carbon nanotube (SWNT) configured as field effect transistor to detect dynamic cellular activities, in particular the time course of cytokines secreted from immune cells or adipose cells and bioelectrical activities of ion channels from electrogenic cells. In this thesis, perfectly aligned arrays of long SiNWs were fabricated using top-down CMOS (complementary metal oxide semiconductor) compatible fabrication techniques and standardized in large-scale production of microelectronics. We demonstrate that these nanowire devices are able to detect cytokines secreted from cells with femtomolar sensitivity, high specificity, wide detection range, and ability for parallel multiplexed monitoring. The detection platform provide a novel tool to reveal the poorly understood signaling mechanisms of the molecules as well as their relevance in secretion related disease.